Hubungan Sosiodemografi dan Klinikopatologi dengan Ketahanan Hidup Pasien Kanker Payudara - Jayadi Tejo (Jurnal Biomedika dan Kesehatan, 2022)
Background: The research of breast cancer prognostic factors has been conducting for a long time, but the results still controversial. The research on demography and clinicopathology factors that determine the survival of breast cancer (BC) patients, remains to be done. Methods: The observational analytic with cross-sectional design would be conduct to describe the demographic, clinicopathology, therapy and two years survival of breast cancer patients. The independent variables were age, stage of disease, and molecular subtype. The dependent variable was two years survival. The association between those variables analyzed by bivariate statistic and the significant variables would be analyzed by regression logistic. Results: Most age of breast cancer patients at diagnosis were ≥ 50 years (74.5%). The majority of sociodemographic profiles of BC patients were undergraduate education, private job and married. The main histological type was the invasive ductal carcinoma. More than 50% of the patients were high stage (60.8%) and hormonal receptors molecular subtype (60.7%). Neoadjuvant chemotherapy was given to 40 patients (78.5%), only 9 patients (17.7%) eligible for anti HER-2/neu therapy. There were 42 of patients (82.4%) have two years survival. There weren’t association between age (p=0.586), stage of disease (p=0.223), molecular subtype (p=0.223) with two years survival of breast cancer patients. Conclusions: The common risk factors of breast cancer is increasing age. Most of breast cancer patients presenting high stage and hormone receptors positive of BC. Although there weren’t significance association, the prevalence low stage BC patients had higher two years survival.